Stariji nazivi za strane svijeta i vjetrove ili Madžarac od ponoća - Kolenić, Ljiljana (SlavVaria, 2026)
Older names for the cardinal points and winds or The Hungarian wind that blows from midnight. Old Croatian names for the winds and the cardinal directions were always connected in meaning.Winds were often named after the cardinal directions. The article discusses Croatian names for winds and the cardinal points in old Croatian dictionaries and in the ethnographic records of Luka Lukić and Ivan Filipovac in the Vinkovci and Brod areas.The formation suffixes for winds largely coincide in the past and today such as suffix -njak (zapadnjak, istočnjak, polnoćnjak, sučenjak, podsučenjak), suffix -ac/-ec (dolnjac, gornjac, madžarac, sremac, zdolec, zgorec). Previously, winds could have the same name as the cardinal direction - west (zapad), south (jug), while today the south wind ends with the suffix -o (jugo), and the west wind with the suffix -njak (zapadnjak). We often find compound names made up of the adjective and noun such as west wind (zapadni vjetar), east wind (istočni vjetar). Some old names refer to the country or area from which the wind blows (madžarac – Hungary, grik – Greece, sremac – Srijem). The names for the sides of the world may be the same in the past and today: istok (east), zapad (west), sjever/siver/sever (north), jug (south). The names for the west in old texts are zapad, zašad, sunčeni zahod, sunčeni zapad, sunac zapada. The names for the east in old texts are istok, ustok, izhod sunčeni, sunčeni istok, sunac istoka. The names for the north in old texts are: sjever/siver/sever (north), polnoć/ponoć (midnight). Polnoć/ponoć (midnight) is the old Slavic name for midnight and for the north side of the world. The names for the south in old texts are jug (south) and poldne/podne (noon). Podne/poldne is the old Slavic name for noon and south side of the world.